Uso e manutenção de próteses dentárias por idosos institucionalizados - Mazini, Rafael Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The Brazilian population pyramid has been modified over the past few years, with increasingly significant proportion of the elderly population, resulting in a fast and intense population aging process, due to rising life expectancy at birth resulting from improvements in sanitation basic health conditions, among other factors. The proposal in this study was to evaluate the use and maintenance of prostheses of institutionalized elderly. It is through a descriptive study covering three elderly nursing homes in the municipality of Araçatuba. The interviews were conducted by a single trained investigator, through a script composed of 16 multiple choice questions related to the characterization of the population analyzed and dental variables: age, gender, type of prosthesis, maintenance and care of the prosthesis, duration of use, adaptation, hygiene prosthodontics and oral and guidance received. It could be concluded with this study that some elderly people were not using dentures for the lack of adaptation. Therefore, it is important to consider the patient's will beyond the biological variables for oral rehabilitation. Although most state do the cleaning, some did not remove for it or even to sleep

A pirâmide populacional brasileira tem sofrido modificações ao longo dos últimos anos, com proporção cada vez mais significativa dos idosos, resultando num processo de envelhecimento populacional rápido e intenso. A proposta no presente trabalho foi avaliar o uso e manutenção das próteses de idosos institucionalizados. Trata-se um um estudo tipo inquérito abrangendo idosos dos 3 asilos existentes no município de Araçatuba. As entrevistas foram realizadas por apenas um pesquisador treinado, composto por um roteiro de 16 questões fechadas relacionadas à caracterização da população analisada e variáveis odontológicas: idade, gênero; tipo de prótese, manutenção e cuidados com as próteses; tempo de uso; adaptação; higienização protética e bucal e orientação recebida. Foi possível concluir com o presente estudo que alguns idosos não estavam utilizando próteses dentárias pela falta de adaptação. Diante disso, é importante considerar a vontade do paciente além das variáveis biológicas para reabilitação bucal. Embora a maioria afirmou realizar a higienização, alguns não retiravam para realizá-la ou até para dormir
Keywords: Saúde bucal; Idosos; Epidemiologia; Oral health